The comparative benefits and drawbacks of equity-based investment versus token-based investment models in achieving scalability and profitability for startups (in the US) - Peled, Omri (2025)
This research examines the comparative benefits and drawbacks of equity-based investment versus token-based funding models, particularly in the US market, as it is the biggest hub of financing, both VC and ICO based startups.